The Concept of Pre-marital Taaruf in Building Harmonious Families at Yayasan Amal Jariyah Indonesia, South Sulawesi - Muhammad Saeful Haq; Hannani; Zainal Said; Dzulkifli Al’Amin; Andi Muh. Taqiyuddin BN (Yayasan pendidikan dzurriyatul Quran, 2026)
The increasing need for a sharia-compliant pre-marital acquaintance model amid widespread free association and high divorce rates has positioned taaruf as a relevant alternative for preparing prospective couples. This study aims to describe the concept of pre-marital taaruf applied at Yayasan Amal Jariyah Indonesia (YAJI) in South Sulawesi, to analyze its implications for forming a harmonious family, and to identify its supporting and inhibiting factors. This research employed a qualitative approach with an intrinsic case-study design; data were collected through in-depth interviews, observation, and documentation involving foundation administrators, taaruf mentors, and program alumni, and were analyzed through data reduction, data display, and conclusion drawing with source triangulation. The results show that taaruf at YAJI is implemented through structured stages, namely biodata submission, kafaah-based matching, istikharah, gradual biodata exchange, nazhar, khitbah, and marriage, under mediator guidance and family involvement while maintaining sharia principles. Taaruf positively contributes to family harmony through information openness, shared religious values, character understanding, effective communication, and continuous post-marital mentoring, indicated by the absence of divorce among alumni couples. The main supporting factors include shared vision, openness, family support, mediator guidance, and sustainable mentoring, whereas the inhibiting factors involve socio-cultural considerations of kafaah (ethnicity and family background) and the limited number of marriage-ready male participants. This study concludes that institutionally managed taaruf constitutes a sharia-based pre-marital mentoring model that constructively shapes harmonious families through the integration of Islamic values, institutional guidance, and family support. The increasing need for a sharia-compliant pre-marital acquaintance model amid widespread free association and high divorce rates has positioned taaruf as a relevant alternative for preparing prospective couples. This study aims to describe the concept of pre-marital taaruf applied at Yayasan Amal Jariyah Indonesia (YAJI) in South Sulawesi, to analyze its implications for forming a harmonious family, and to identify its supporting and inhibiting factors. This research employed a qualitative approach with an intrinsic case-study design; data were collected through in-depth interviews, observation, and documentation involving foundation administrators, taaruf mentors, and program alumni, and were analyzed through data reduction, data display, and conclusion drawing with source triangulation. The results show that taaruf at YAJI is implemented through structured stages, namely biodata submission, kafaah-based matching, istikharah, gradual biodata exchange, nazhar, khitbah, and marriage, under mediator guidance and family involvement while maintaining sharia principles. Taaruf positively contributes to family harmony through information openness, shared religious values, character understanding, effective communication, and continuous post-marital mentoring, indicated by the absence of divorce among alumni couples. The main supporting factors include shared vision, openness, family support, mediator guidance, and sustainable mentoring, whereas the inhibiting factors involve socio-cultural considerations of kafaah (ethnicity and family background) and the limited number of marriage-ready male participants. This study concludes that institutionally managed taaruf constitutes a sharia-based pre-marital mentoring model that constructively shapes harmonious families through the integration of Islamic values, institutional guidance, and family support.